PENINGKATAN PENGETAHUAN KADER DALAM DETEKSI DINI TB PARU DENGAN MODUL DETEKSI DINI TB PARU - Fariji, A Achmad; Sugiri, Herry (Jurnal Kesehatan Siliwangi, 2023)
The number of new TB cases in 2018 was 1,308. Meanwhile, child TB cases in 2018 were 138. The realization or achievement of TB control program performance of 78.80% has actually reached or even exceeded the program target, but in terms of minimum service it has not yet reached 100% because TB case detection has not yet reached 100%. Active case finding, administering IEC to prevent transmission by implementing cough etiquette, controlling risk factors and administering preventive medication. The principle of TB services is finding people with TB as early as possible, managing them according to standards as well as monitoring them until they recover through Find, Treat Until Heal. TB case detection has not yet reached 100%. To increase case findings through early detection activities, the role of posyandu cadres has a very big influence in increasing case findings through early detection. This research uses quasi-experiment. The results of the analysis showed that there was a significant difference in knowledge scores between the pretest and posttest scores in each group. The results of the independent t test analysis showed differences in results between the intervention group and the control group, meaning that the use of the module was more effective in increasing cadres' knowledge. It is recommended to provide the module to cadres to increase knowledge and actively promote health activities in TB case screening.